Genetic Differentiation of Bisexual and Parthenogenetic Populations of Plant Louse Cacopsylla ledi (Hemiptera, Psylloidea) - Shapoval, Nazar A.; Nokkala, Seppo; Nokkala, Christina; Shapoval, Galina N.; Labina, Eugenia S.; Romanovich, Anna E.; Kuznetsova, Valentina G. (MDPI AG, 2026)
The psyllid genus Cacopsylla comprises mainly bisexually reproducing species; however, some members of this genus exhibit a unisexual mode of reproduction. Using an integrative approach that combines molecular and cytogenetic methods, as well as Wolbachia screening, we conducted a comprehensive study of the Palaearctic species C. ledi. We show that this species uses various reproductive strategies (bisexual and parthenogenetic) across its distribution range. Our findings indicate that the bisexual mode of reproduction has emerged at least twice in the evolutionary history of C. ledi. Bisexual populations in southern Fennoscandia are of ancestral origin, whereas the bisexual mode of reproduction observed in northern Fennoscandia represents a recent secondary transition from parthenogenesis. We report that in the first case, parthenogenetic and bisexual lineages can be easily distinguished not only cytogenetically but also by DNA barcoding, while in the second case, “bisexual” individuals share DNA barcodes with parthenogenetic ones. A comprehensive Wolbachia screening (1140 specimens across the entire distribution range) revealed Wolbachia infection in every specimen of C. ledi, indicating a significant role of the endosymbiont in the biology and evolution of this species.